Sosialisasi Proses Pengeringan Ikan Di Jembatan Puri, Kelurahan Klaligi, Kecamatan Sorong Manoi, Kota Sorong: Sosialisasi Proses Pengeringan Ikan Di Jembatan Puri, Kelurahan Klaligi, Kecamatan Sorong Manoi, Kota Sorong - Christy Radjawane1; M. Iksan Badaruddin; Fatimah Hardanti; Ellen Loupatty (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2023)
Klaligi Village has a small group of Indigenous Papuans (OAP) who are quite active in the process of making dried fish, the process of making dried fish carried out by the community changes several types of fish including puri fish and other caught fish. Drying is a process of reducing the water content of the material until it reaches a certain desired moisture content so that it can slow down the rate of product deterioration due to biological and chemical activities. The purpose of drying itself is to reduce the moisture content of the material to the extent that the development of microorganisms and the activity of enzymes that can cause decay are inhibited or even completely stopped. The objectives of this community service activity are 1) Initial counseling about the Drying Process, thereby increasing the knowledge and abilities of the community, especially IRT OAP, on how to process various kinds of JEMPUR (Jembatan Puri) dried fish and improve the quality of dried fish. The process of drying fish can be carried out by coastal communities if they pay attention to the area of ​​fish and thickness of fish meat, temperature, air movement speed, air humidity, atmospheric pressure, water evaporation and drying time, fish drying process can be done to improve the economy of coastal communities.